Block Bootstrap Theory for Multivariate Integrated and Cointegrated Processes - Carsten Jentsch; Efstathios Paparoditis; Dimitris N. Politis (University of Mannheim, Department of Economics, 2014)
We develop some asymptotic theory for applications of block bootstrap resampling schemes to multivariate integrated and cointegrated time series. It is proved that a multivariate, continuous-path block bootstrap scheme applied to a full rank integrated process, succeeds in estimating consistently the distribution of the least squares estimators in both, the regression and the spurious regression case. Furthermore, it is shown that the same block resampling scheme does not succeed in estimating the distribution of the parameter estimators in the case of cointegrated time series. For this situation, a modified block resampling scheme, the so-called residual based block bootstrap, is investigated and its validity for approximating the distribution of the regression parameters is established. The performance of the proposed block bootstrap procedures is illustrated in a short simulation study.
urn:nbn:de:bsz:180-madoc-366688
Keywords: C15; C32; 330; Block bootstrap; bootstrap consistency; spurious regression; functional limit theorem; continuous-path block bootstrap; model-based block bootstrap